Soluções do problema de Plateau mergulhadas. - Gama, Eddygledson Souza (2015)
This dissertation is divided into three chapters. In the first chapter is done a brief introduction of the main tools necessary for the development of this work. On the other hand, in the second chapter, the problem of Plateau for convex manifolds is defined, and it shows the existence of solutions of such problem in this ambient. The third and last part of this work is dedicated to proving a result that guarantees that over certain conditions the solution of the Plateau problem is an embedded. In particular, as an application of this result, it obtains a version of Dehn’s lemma for analytic and convex manifolds.